Quest for Agency in African and Indian Theologies and the Way Forward - Savariyar, Dhinakaran (Asian Horizons, 2020)
African and Indian theologies share much in common and an important point of interface is their quest for ‘Agency’ in doing theology. Decolonization, contextualization and inculturation are some successful attempts by both that have attracted the attention of universal churches in so far as they have adequately represented their voices. This identity-seeking has been spearheaded by Laurenti Magesa in Africa and Michael Amaladoss in India. However, the journey ahead looks very promising because theologizing attempts are quite interdisciplinary today. Catholic theological ethics in both continents has redefined the approach by its distinct claim for ‘inculturation in ethics.’ Its emphasis on the role of culture in ethics or ethical formation has given a new focus to the search in both continents. In sum, the ‘Agency Question’ that unites both discovers its root in ‘inculturated Gospel’ especially by attributing sacramental value to cultural forms and expressions in their respective cultures.